Holding out for hope: discourses of dementia and their implications for care on an acute organic assessment and treatment ward - Matkin, Hannah (2019)
The needs of individuals who receive a diagnosis of dementia can be complex, and can pose a challenge to those who care for them. Discourses around the construct of dementia have evolved over time, which has influenced care practices and policies. The way that healthcare professionals construct dementia may have important implications for the care that is provided. This article uses naturally occurring talk from an acute organic assessment and treatment ward to explore how staff construct dementia. A Foucauldian form of discourse analysis was used to analyse talk from fifteen multidisciplinary healthcare professionals. In this article we present a reading of this talk, where dementia is constructed as: an unstable inner state that can fluctuate in severity, an illness that will inevitably progress, and a condition that can take away a person’s insight. Implications for care resulting from these discourses is considered through examining the subject positions that were made available. A final discourse relevant to care practices was identified, where healthcare professionals resisted a dominant medical discourse, which opened up space for hope and innovative care practices.